Going to green. Volume 3, Balancing green space with the built environment [videorecording (DVD)] - Wiland, Harry; Bell, Dale, 1938-; D'Agnese, Joseph; Kiernan, Denise (PBS Home Video, 2009)
"Going to Green deals with the restoration of America's urban landscape through the creation of sustainable neighborhood ecosystems. Each chapter is devoted to a specific subject and is accompanied by a lesson with service learning extension activities"--Container.